A national survey of NICU parents and neonatologists on 21st Century Cures Act awareness - Ho, Timmy; Kalluri, Nikita S.; Cordova-Ramos, Erika G.; Fraust-Wylie, Molly; Parker, Margaret G. (Journal of perinatology, 2025)
Parents (N = 99) Neonatologists (N = 213) Improves communication 4.63 (SD = 0.57) 2.99 (SD = 0.95) Improves family understanding 4.62 (SD = 0.60) 2.77 (SD = 1.04) Improves family satisfaction 4.32 (SD = 0.76) 3.28 (SD = 0.99) Improves healthcare quality 4.24 (SD = 0.83) 2.68 (SD = 0.92) Let all families access equally 4.20 (SD = 1.00) 2.90 (SD = 1.21) Important in the NICU setting 4.64 (SD = 0.59) 2.78 (SD = 1.04) Decreases health inequities 3.86 (SD = 1.00) 2.50 (SD = 1.01) aFactors of interest were measured as 5-point Likert scales assessing agreement to the statement:“Parental access to health information…,” with 1 as strongly disagree, 2 as disagree, 3 as neutral, 4 as agree, and 5 as strongly agree. Author contributions TH and MGP conceptualized and designed the study, coordinated and supervised data collection, participated in data collection, participated in data interpretation, helped draft the initial manuscript, and reviewed and revised the manuscript. NSK, EGC, and MFW participated in data collection, participated in data interpretation, and reviewed and revised the manuscript.